Financial development and business growth: A case of the Southern Key Economic Region - Minh Ngoc Ngo; Thuc Ngoc Nguyen (Cogent Economics & Finance)
This paper employs generalized methods of moment (GMM) to analyze the enterprise data set collected from the General Statistics Office in the period 2005–2018 to provide insight on the influence of financial development on business growth: the case of the Southern Key Economic Zone (SKEZ). The empirical results indicate that financial development plays an important role in business growth. However, providing financing to offset scale has the potential to increase sales but reduce business growth. Thus, businesses in the SKEZ need to carry out some following points. First, corporate managers not only focus on growth and considering as important as sales and productivity throughout their operations but on strengthening the depth of the financial system to allow businesses to get favorable conditions to receive external financial sources. Second, policymakers should promote a well-developed financial system that can ease credit constraints for businesses.